Emulsion liquid membrane technology in organic acid purification [Teknologi emulsi membran cecair dalam penulenan asid organik] - Jusoh, Norela (Malaysian Society of Analytical Sciences, 2016)
Emulsion Liquid Membrane (ELM) process have shown a great potential in wide application of industrial separations such as in removal of many chemicals, organic compounds, metal ions, pollutants and biomolecules. This system promote many advantages including simple operation, high selectivity, low energy requirement, and single stage extraction and stripping process. One potential application of ELM is in the purification of succinic acid from fermentation broth. This study outline steps for developing emulsion liquid membrane process in purification of succinic acid. The steps include liquid membrane formulation, ELM stability and ELM extraction of succinic acid. Several carrier, diluent and stripping agent was screened to find appropriate membrane formulation. After that, ELM stability was investigated to enhance the recovery of succinic acid. Finally, the performance of ELM was evaluated in the extraction process. Results show that formulated liquid membrane using Amberlite LA2 as carrier, palm oil as diluent and sodium carbonate, Na2CO3 as stripping agent provide good performance in purification. On the other hand, the prepared emulsion was observed to be stable up to 1 hour and sufficient for extraction process. In conclusion, ELM has high potential to purify succinic acid from fermentation broth.